Gastric emptying of carbohydrate drinks in term parturients before elective caesarean delivery: an observational study. (February 2020) - Popivanov, P.; Irwin, R.; Walsh, M.; Leonard, M.; Tan, T.
Highlights: Gastric emptying of carbohydrate (CHO) drink 400 mL was investigated. 40 term patients before elective caesarean delivery. All reached a qualitative gastric grade of 0 or 1 by 100 min after consumption. 400 mL CHO drink can be consumed up to 2 h before elective surgery. Abstract: Background: Pre-operative carbohydrate (CHO) drinks have shown some benefits peri-operatively and have been incorporated into many Enhanced Recovery after Surgery (ERAS) programmes. We assessed the gastric emptying of pre-operative CHO drinks prior to elective caesarean delivery using ultrasonography. Methods: After a standard overnight fast, non-labouring pregnant women awaiting elective caesarean delivery underwent a standardised gastric ultrasound assessment at baseline and then every 20 min for 2 h after consuming 400 mL of a CHO drink. The gastric emptying was determined at each time-point both qualitatively and quantitatively. The primary outcome was the time taken for participants to return to a qualitative fasted Perlas grade of 0 or 1. Results: The gastric emptying of 40 participants was analysed. At baseline, all patients had a qualitative grade of either 0 or 1. All patients had returned to either grade 0 or 1 by 100 min. At 120 min the antral right lateral decubitus (RLD) cross-sectional area (CSA) was 8.03 cm 2 (95th percentile; 95% CI 7.4 to 8.3 cm 2 ) and gastric volume per kg was 1.57 mL/kg (95th percentile; 95% CI 1.4 to 2.2). At 120 min there was no statistically significant difference from baseline for the RLD CSA ( P =0.38) or gastric volume per kg ( P =0.27). Conclusions: The gastric emptying of this cohort of pregnant women suggests that 400 mL of a CHO drink can be safely consumed up to two hours before elective surgery. This study can help inform future peri-operative fasting guidelines for pregnant patients.